Dampak Moderasi Perilaku Knowledge Sharing dan Teamwork terhadap Produktivitas Dosen - Fenri Abraham Stevi Tupamahu; Merryll Pelamonia; Wiclif S. Pinoa (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2020)
Abstract: This study aims to: (1) examine the effect of teamwork work activities on the productivity of lecturers at the Faculty of Social Sciences, Pattimura University; and (2) determine the role of moderating knowledge sharing behavior between the effects of teamwork work activities on the productivity of lecturers at the Faculty of Social Sciences, Pattimura University. This type of research is causal research. The unit of analysis in this study was the individual lecturer at the Social Sciences Department of the Faculty of Teacher Training and Education at Pattimura University. The total number of lecturers at the Faculty of Social Sciences, Pattimura University is 72 people. The sampling method uses nonprobability methods, sampling using purposive sampling technique. Determination of the sample is based on judgment (judgment sampling). The results of the study explain that knowledge sharing behavior is not a variable that directly affects the productivity of Social Sciences lecturers at the Faculty of Social Sciences, Pattimura University, but interacts with teamwork.  Abstrak: Penelitian ini bertujuan: (1) menguji pengaruh aktivitas kerja teamwork terhadap produktivitas dosen Jurusan IPS FKIP Universitas Pattimura; dan (2) menentukan peran moderasi perilaku knowledge sharing antara pengaruh aktivitas kerja teamwork terhadap produktivitas dosen Jurusan IPS FKIP Universitas Pattimura. Jenis penelitian ini merupakan riset causal. Unit analisis pada penelitian ini adalah individu dosen Jurusan IPS FKIP Universitas Pattimura. Keseluruhan jumlah dosen Jurusan IPS FKIP Universitas Pattimura sebanyak 72 orang. Metode pengambilan sampel menggunakan metode nonprobabilitas, pengambilan sampel menggunakan teknik purposive sampling. Penentuan sampel berdasarkan pertimbangan (judgment sampling). Hasil penelitian menjelaskan perilaku knowledge sharing tidak sebagai variabel yang mempengaruhi langsung terhadap produktivitas dosen Jurusan IPS FKIP Universitas Pattimura, namun berinteraksi terhadap teamwork.